2013
DOI: 10.4269/ajtmh.12-0550
|View full text |Cite
|
Sign up to set email alerts
|

High Anti-Cryptosporidium parvum IgG Seroprevalence in HIV-Infected Adults in Limpopo, South Africa

Abstract: Abstract. A seroepidemiological study was performed to determine the seroprevalence of Cryptosporidium in human immunodeficiency virus (HIV)-infected adults and local university students in the Limpopo Province, South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Both the HIV positive and HIV negatives were infected with Cryptosporidium spp; but PLWH had the highest prevalence of Cryptosporidium spp (16.8%). The prevalence of Cryptosporidium spp in this study is lower unlike the 44% reported earlier in Cameroon [15] and the 79.0%, in South Africa [43]. Cryptosporidium spp is recognized as an opportunistic parasite in HIV/AIDS patients because it tends to be present when the CD4 + T cell counts are below 200 cells/µL.…”
Section: Discussioncontrasting
confidence: 77%
“…Both the HIV positive and HIV negatives were infected with Cryptosporidium spp; but PLWH had the highest prevalence of Cryptosporidium spp (16.8%). The prevalence of Cryptosporidium spp in this study is lower unlike the 44% reported earlier in Cameroon [15] and the 79.0%, in South Africa [43]. Cryptosporidium spp is recognized as an opportunistic parasite in HIV/AIDS patients because it tends to be present when the CD4 + T cell counts are below 200 cells/µL.…”
Section: Discussioncontrasting
confidence: 77%
“…In this investigation, we detected higher seroprevalence (10/311, 3.22%) of Cryptosporidium infection in parrots compared with Sheather's sugar flotation technique. This is because ELISA usually has better sensitivity for the detection of antibodies against Cryptosporidium [ 31 ]. Moreover, parrots which were positive for Cryptosporidium oocysts in fecal samples were also positive for indirect ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…While recurrence was unlikely within one month of infection in one cohort [ 82 ], by nine weeks post-infection only 54% of children in a different study demonstrated antibody to an immunodominant Cryptosporidium antigen gp15 through nine weeks [ 83 ]. Although humoral and cell-mediated responses to specific Cryptosporidium antigens are not universally concordant [ 20 , 84 ], these findings suggest that immunity in children may rapidly wane. Also, our findings are restricted to homologous C .…”
Section: Discussionmentioning
confidence: 99%